Molecular identification of iron oxidizing bacteria isolated from acid mine drainages in Peru - Abanto, M (2013)
This work was supported in part by CONCYTEC grant 198-2005. Yanacocha and SPCC mining for providing the samples. M.A. was the recipient CONCYTEC Master in Molecular Biology scholarship